Response Bias Cannot Explain Action-Specific Effects: Evidence from Compliant and Non-Compliant Participants. (February 2013) - Witt, Jessica K; Sugovic, Mila
According to the action-specific account of perception, the perceiver's ability to act influences perception of the target. For example, targets that are easier to acquire are reported to look closer, bigger, and slower. However, an alternative explanation for these effects is that they are due to response bias, rather than to changes in perception. To test the role of response bias, we employed two separate manipulations. We manipulated people's abilities to block a ball and measured the corresponding effects on estimated ball speed. We also created an explicit task demand by giving participants instructions that emphasized responding either slow or fast. Participants were grouped, based on whether they were compliant or non-compliant with the instructions. Regardless of their compliance, we found an action-specific effect of blocking ability on estimated speed. Given that non-compliant participants still showed the effect, the results provide strong evidence against a response-bias explanation of this action-specific effect. Paired with earlier research, we conclude that blocking ability influences perceived speed. Perception expresses the relationship between the environment and the perceiver, and this view is consistent with emerging neural and behavioral evidence for an interconnected perceptual–motor system.